(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2017)
This paper presents the research methods developed to investigate the knowledge construction process of students and how they understand the concept of internal resistance as represented by the everyday situation in which an electric shower causes the light of a light bulb to dim when turned on. The theoretical framework for this study is based on the Piagetian genetic epistemology and the linear circuit theory. The methodology was developed based on a qualitative approach, using the multiple-case study strategy. The semi-structured interviews were inspired by and adapted from the Piagetian clinical method in order to identify and analyze the students’ explanations and associations regarding the theoretical model that explains the phenomenon. The goal is to make this paper available for teachers as a reference material and an encouragement to reflect about their own teaching practices so they can develop pedagogical actions to assist the students’ learning process in vocational courses on Electricity, Electronics and similar areas in both secondary and higher education. The paper provides detailed information about the development and improvement of the data collection tool, includes answers from the subjects interviewed, reflects on the method’s concerns and benefits to allow for the grasp of knowledge of other points of view, and, finally, discusses the possibilities of developing activities that are more interactive and forward-looking for the students.